2018
DOI: 10.3310/hta22080
|View full text |Cite
|
Sign up to set email alerts
|

The West Midlands ActiVe lifestyle and healthy Eating in School children (WAVES) study: a cluster randomised controlled trial testing the clinical effectiveness and cost-effectiveness of a multifaceted obesity prevention intervention programme targeted at children aged 6–7 years

Abstract: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 8. See the NIHR Journals Library website for further project information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 89 publications
0
65
0
1
Order By: Relevance
“…Eight studies were conducted in the USA [34, 36, 41, 44-46, 48, 53], and six were from Australia [30,33,40,42,47,49]. The rest were conducted in Great Britain (n = 5) [24,27,32,37,38], Ireland (n = 2) [29,52], Germany (n = 1) [39], China (n = 1) [35], South Korea (n = 1) [54], Canada (n = 1) [28], Denmark (n = 1) [31], Spain (n = 2) [43,51], Norway (n = 1) [50] and Turkey (n = 2) [25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were conducted in the USA [34, 36, 41, 44-46, 48, 53], and six were from Australia [30,33,40,42,47,49]. The rest were conducted in Great Britain (n = 5) [24,27,32,37,38], Ireland (n = 2) [29,52], Germany (n = 1) [39], China (n = 1) [35], South Korea (n = 1) [54], Canada (n = 1) [28], Denmark (n = 1) [31], Spain (n = 2) [43,51], Norway (n = 1) [50] and Turkey (n = 2) [25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The duration of the interventions varied from 4 weeks to 4 years. The level of implementation reach was low in six studies [24,27,28,30,38,48], medium in two studies [32,41], high in eighteen studies [25, 31, 33, 34, 36, 37, 39, 40, 42-47, 49-51, 53] and unknown in five studies [26,29,35,52,54]. A description of qualitative implementation factors (fidelity, dose delivered or received, responsiveness, level of adaptation) is shown in Online resource 3.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Within the trial, proportionally more children within the intervention arm (10%) compared to the control arm (7%) transitioned from a baseline healthy weight to a state defined as having obesity at follow up two. A multilevel logit model from the main trial analysis [29] demonstrated that the odds ratio associated with children in the intervention arm transitioning to living with obesity at follow up two, was 1.17 (0.66, 2.09), when controlling for pre-specified covariates. Although this was not a statistically significant difference, this estimated effect in favour of the control arm made the planned economic analysis for estimating the cost per ‘case of childhood obesity prevented’ not possible, that is, the control arm dominated the intervention arm.…”
Section: Resultsmentioning
confidence: 99%
“…However, obesity prevalence in the participating schools was compared with the prevalence estimated from the National Child Measurement Programme at the time and was found to be similar. 31 Comparisons of demographic characteristics of children with and without parental consent to participate in the WAVES trial (undertaken as part of the WAVES trial) also did not show major differences, 32 suggesting that the study sample is broadly representative.…”
Section: Discussionmentioning
confidence: 97%